Effect of inspiratory muscle training on performance of handball athletes - Hartz, C. S.; Sindorf, M. A. G.; Lopes, C. R.; Batista, J.; Moreno, M. A. (Journal of Human Kinetics, 2018)
Inspiratory muscle training (IMT) is a strategy that has been used to improve performance in different sports modalities. This study investigated the effects of an IMT program on respiratory muscle strength and resistance as well as aerobic physical performance (PP) of handball athletes. Nineteen 20 ± 3 year-old male athletes were allocated into an experimental (EG, n = 10) or a placebo group (PG, n = 9). Their respiratory muscle strength was evaluated by measuring the maximum inspiratory and expiratory pressures (MIP and MEP), muscular respiratory resistance by maximum voluntary ventilation (MVV) and aerobic PP by the cardiopulmonary exercise test. The study was designed to evaluate the effects of a 12-week IMT program with five sessions a week. A significant difference was observed in the pre and post IMT values of the MIP (170 ± 34 to 262 ± 33 cmH2O) and MEP (177 ± 36 to 218 ± 37 cmH2O) in the EG, and MIP (173 ± 45 to 213 ± 21 cmH2O) in the PG, with a large effect size for the MIP, when the groups were compared. MVV showed a significant increase (162 ± 24 to 173 ± 30 L) in the EG, with a small effect size. There was a significant difference in maximum oxygen uptake (54 ± 8 to 60 ± 7 ml/kg/min) in aerobic PP. Oxygen uptake at the respiratory compensation point (RCP) (46 ± 6 to 50 ± 5 ml/kg/min), with a moderate effect size for both variables, was observed in the EG after IMT. We concluded that IMT provided a significant increase in respiratory muscle strength and resistance,